2007
DOI: 10.1128/jvi.02171-06
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Saimiri Episomal Persistence Is Maintained via Interaction between Open Reading Frame 73 and the Cellular Chromosome-Associated Protein MeCP2

Abstract: Herpesvirus saimiri (HVS) is the prototype gamma-2 herpesvirus, which naturally infects the squirrel monkey Saimiri sciureus, causing an asymptomatic but persistent infection. The latent phase of gamma-2 herpesviruses is characterized by their ability to persist in a dividing cell population while expressing a limited subset of latency-associated genes. In HVS only three genes, open reading frame 71 (ORF71), ORF72, and ORF73, are expressed from a polycistronic mRNA. ORF73 has been shown to be the only gene ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
38
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 47 publications
0
38
1
Order By: Relevance
“…The viral genome exists as a stable circular episome separate from host DNA, thereby reducing the risk of insertional mutagenesis and gene silencing by epigenetic mechanisms. HVS can also persist in dividing cells, as the episomal DNA is able to replicate during latency and is transferred to daughter cells upon cell division via the open reading frame 73 (ORF73) episomal maintenance protein (22)(23)(24)(25). The virus has also been shown to efficiently infect and persist in three-dimensional multicellular spheroid cultures, a three-dimensional cell culture system that closely resembles a tumor, in addition to tumor xenografts in vivo (26)(27)(28).…”
mentioning
confidence: 99%
“…The viral genome exists as a stable circular episome separate from host DNA, thereby reducing the risk of insertional mutagenesis and gene silencing by epigenetic mechanisms. HVS can also persist in dividing cells, as the episomal DNA is able to replicate during latency and is transferred to daughter cells upon cell division via the open reading frame 73 (ORF73) episomal maintenance protein (22)(23)(24)(25). The virus has also been shown to efficiently infect and persist in three-dimensional multicellular spheroid cultures, a three-dimensional cell culture system that closely resembles a tumor, in addition to tumor xenografts in vivo (26)(27)(28).…”
mentioning
confidence: 99%
“…We have recently demonstrated that HVS ORF73 associates with MeCP2 and shown that this association is essential for HVS chromosomal attachment and episomal persistence (Griffiths & Whitehouse, 2007). In this report, we have investigated whether HVS ORF73 interacts with other chromosome-associated proteins to ensure mitotic chromosome association.…”
mentioning
confidence: 99%
“…293T cells were cotransfected with pEGFP-HistoneH1 in the presence of pMyc or p73-myc (Calderwood et al, 2004a). To ensure that the interaction between ORF73 and HistoneH1 was not due to a common affinity for DNA, co-immunoprecipitation assays were performed with cell extracts which remained untreated or treated with DNase I, as described previously (Griffiths & Whitehouse, 2007). To confirm that DNase I treatment had been successful, untreated and treated cell extracts were used as templates within a PCR utilizing primers directed against glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
mentioning
confidence: 99%
See 2 more Smart Citations